2020
DOI: 10.1111/joa.13204
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of the larynx and trachea in echolocating and non‐echolocating bats

Abstract: The synchronization of flight mechanics with respiration and echolocation call emission by bats, while economizing these behaviors, presumably puts compressive loads on the cartilaginous rings that hold open the respiratory tract. Previous work has shown that during postnatal development of Artibeus jamaicensis (Phyllostomidae), the onset of adult echolocation call emission rate coincides with calcification of the larynx, and the development of flight coincides with tracheal ring calcification. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…This prediction does not match the pattern of calcification we found in our rat larynges, which were mainly calcified in areas that can be under significant deformation pressure, specifically the specific areas of vocal fold attachment. Carter (2020) compared calcifications in the trachea and larynx across laryngeally echolocating bats and found that higher‐intensity vocalizing species tend to have a more mineralized thyroid cartilages than lower‐intensity species. Thyroid mineralization in the high line rats might help to facilitate and sustain USV production, similar to that observed in laryngeally echolocating bats.…”
Section: Discussionmentioning
confidence: 99%
“…This prediction does not match the pattern of calcification we found in our rat larynges, which were mainly calcified in areas that can be under significant deformation pressure, specifically the specific areas of vocal fold attachment. Carter (2020) compared calcifications in the trachea and larynx across laryngeally echolocating bats and found that higher‐intensity vocalizing species tend to have a more mineralized thyroid cartilages than lower‐intensity species. Thyroid mineralization in the high line rats might help to facilitate and sustain USV production, similar to that observed in laryngeally echolocating bats.…”
Section: Discussionmentioning
confidence: 99%
“…Although stylohyal morphology and its articulation with the tympanic bone show high similarity between different families of laryngeally echolocating bats (Carter, 2020; Sprague, 1943; Veselka et al, 2010), there is variation in the morphology of the more proximal elements of the anterior cornu of hyoid apparatus. For example, there is a tendency towards reduction of the hypohyal in length, with this reduction reaching its extreme in Eptesicus , Minipterus , and Kerivoula , where it is present as a slender fascial attachment of the anterior cornu to the basihyal (Sprague, 1943).…”
Section: Discussionmentioning
confidence: 99%
“…Laryngeally echolocating bats exhibit many adaptations associated with the production and reception of sophisticated call sequences. For example, echolocation is coupled with laryngeal cartilage that is structurally reinforced through extensive calcification or ossification, presumably in response to the increased mechanical demands during vocalization (Carter, 2020; Carter & Adams, 2014; Denny, 1976; Griffiths, 1978; Suthers, 2004). Additionally, the cochleae of laryngeally echolocating bats have enlarged basal turns relative to other mammals and internal adaptations that increase the stiffness of the basilar membrane, thereby increasing sensitivity to the higher frequencies associated with echolocation signals (Kössl & Vater, 1995; Vater & Kössl, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations